How to Keep Future Doctors Awake: An Inquiry into Online Learning Video Design Preferences Among Medical Students - Himel Mondal; Koushik Saha; Shaikat Mondal (Galician Medical Journal)
Introduction. Online learning has become increasingly prevalent in medical education, offering flexibility and accessibility to undergraduate medical students. However, the design of online learning materials, particularly videos, plays a crucial role in engaging students and promoting effective learning. Understanding the preferences of undergraduate medical students regarding video design is essential for creating videos that meet their needs and enhance their educational experience. Therefore, this study aims to explore the design preferences of undergraduate medical students for learning videos.